(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
A Coral fauna has been collected in the calcareous/arenitic shallow-water units of Artinskian/Kubergandian ages in Northern Karakorum (Hunza valley) and Aghil Ranges (Shaksgam valley). Most of the species collected were undescribed, but their age is fairly well constrained through fusulinids and conodonts. From the biogeographic point of view they belongs to the Lytvolasma province, with some affinities to Lhasa microplate, Himalaya Range and allochthonous Nappe in Timor.